Low-temperature graphitic formation promoted by confined interphase structures in polyacrylonitrile/carbon nanotube materials. (14th February 2018) - Tajaddod, Navid; Li, Heng; Minus, Marilyn L.
Abstract: In this work polyacrylonitrile (PAN)/single wall carbon nanotube (SWNT) composites with 50 wt% SWNT loading were studied. A previously studied solvent-based phase separation process was used to enhance PAN-SWNT crystallization conditions and interphase formation within the composites. Two types of SWNT species were used here to produce two composites materials with well-ordered PAN-SWNT interphase structures. All precursor composite films were stabilized and subsequently carbonized at temperatures ranging from 900 to 1500 °C under various carbonization times. Wide-angle X-ray diffraction and electron microscopy were used to analyze the structural change in these precursors during carbonization. It was found that ordered graphitic structures were formed using specific temperature/time conditions as early as 900 °C. This low-temperature graphitic structure can be tracked directly to the PAN interphase structure within the precursors. This paper discusses the linkage between precursor PAN-SWNT interphase formation and subsequent low-temperature graphitic formation. Graphical abstract: Image 1 Highlights: Phase separation is used to isolate polyacrylonitrile (PAN)-single-walled carbon nanotubes (SWNT) interphase regions. The comparative importance of PAN crystal formation, as well as confinement at the interphase is highlighted. The formation of interfacial PAN on SWNT and its subsequent conversion to graphite at as early as 900 °C is outlined. High-temperature graphitization is performed to show further perfection of the early onset graphite. This study is focused on understanding the effects of nano-materials on carbonization process-structure relationships.